Into a New Regressive Era: Implications for Public Administration. (14th November 2017) - Box, Richard C.
Abstract : American politics periodically shifts from a progressive orientation toward social change to a regressive orientation. During progressive phases, governmental attention is focused on strengthening the social safety net, protecting minority and immigrant populations, and regulating private sector activities in finance, business, and the physical environment. During regressive phases, legislation and administrative actions are designed to weaken or reverse these measures. In this time of heightened awareness of race, religion, inequality, and environmental change, recent political events signal a widespread reaction to trends in contemporary society and a shift toward a deeply regressive phase in governance. The article examines characteristics of this shift and what it may mean for public administration.